COST OF CAPITAL DETERMINANTS: CONTEXT IN INDONESIA AND MALAYSIA - Widowati, Maduretno; Yuliati, Yuliati; Wahyuningsih, Susanti; Indriyatni, Lies; Widodo, Untung (STIE Pelita Nusantara Semarang, 2025)
The purpose of this paper is to look at the determinants of the cost of capital for a company. This study conducts a literature review with the aim of identifying the factors that affect the cost of capital for a company. The study shows that profitability, liquidity, tax, growth, size, and age of the company are some of the major determinants that affect the cost of capital of the company. The study further shows a positive correlation between the cost of capital and profitability, liquidity, growth, size, and age of the company. The capital arrangement of the company is determined based on the pecking order theory and the trade-off theory while keeping in mind the cost elements associated with it. In Indonesia, economic stability and political stability are the major determinants that determine the cost of capital for a company. These determinants affect the availability and cost.